Alkaloid chemodiversity in Mandragora spp. is associated with loss-of-functionality of MoH6H, a hyoscyamine 6β-hydroxylase gene. (June 2019) - Schlesinger, Daniel; Davidovich Rikanati, Rachel; Volis, Sergei; Faigenboim, Adi; Vendramin, Vera; Cattonaro, Federica; Hooper, Matthew; Oren, Elad; Taylor, Mark; Sitrit, Yaron; Inbar, Moshe; Lewinsohn, Efraim
Highlights: Mandragora spp. accessions show significant alkaloid chemodiversity. M. officinarum and M. turcomanica lack anisodamine and scopolamine. M. autumnalis accumulates hysocyamine, anisodamine and scopolamine. H6H is conserved among scopolamine-producing species but mutated in M. officinarum . H6H from M. autumnalis is functionally active but H6H from M. officinarum is not. Abstract: Mandrakes ( Mandragora spp., Solanaceae) are known to contain tropane alkaloids and have been used since antiquity in traditional medicine. Tropane alkaloids such as scopolamine and hyoscyamine are used in modern medicine to treat pain, motion sickness, as eye pupil dilators and antidotes against organo-phosphate poisoning. Hyoscyamine is converted to 6β-hydroxyhyoscyamine (anisodamine) and scopolamine by hyoscyamine 6β-hydroxylase (H6H), a 2-oxoglutarate dependent dioxygenase. We describe here a marked chemo-diversity in the tropane alkaloid content in Mandragora spp. M. officinarum and M. turcomanica lack anisodamine and scopolamine but display up to 10 fold higher hyoscyamine levels as compared with M. autumnalis . Transcriptomic analyses revealed that H6H is highly conserved among scopolamine-producing Solanaceae. MoH6H present in M. officinarum differs in several amino acid residues including a homozygotic mutation in the substrate binding region of the protein and its prevalence among accessions was confirmed by Cleaved-Amplified-Polymorphic-Sequence analyses. Functional expression revealed that MaH6H, a gene isolated from M. autumnalis encodes an active H6H enzyme while the MoH6H sequence isolated from M. officinarum was functionally inactive. A single G to T mutation in nucleotide 663 of MoH6H is associated with the lack of anisodamine and scopolamine in M. officinalis .